Moneylender Free Village: A Case Study of Fostering Social Piety in the Cikuasa Community, Cilegon City, Indonesia - Muhlisin, Muhlisin; Sahrowiyah, Titin; Maharani, Aulia Raziva; Mauzaniah, Haliza (Cakrawala: Jurnal Studi Islam, 2024)
This study investigates the Moneylender Free Village (MFV) program within the Cikuasa community, Cilegon City, Indonesia, examining its role in fostering Islamic economic principles and social piety. Through qualitative descriptive research involving interviews with 20 purposively selected respondents, this study explores the negative impacts of loan shark practices on the community, the formation and implementation of the MFV program with the guidance of NGOs and Islamic banking, and the subsequent empowerment of social piety among community members. Findings reveal that the MFV program effectively mitigates the detrimental effects of loan sharks, fostering economic stability and social well-being. Furthermore, the study demonstrates how the program contributes to the enhancement of social piety through increased awareness of Allah's supervision, the cultivation of ihsan (excellence in worship and conduct), and the promotion of beneficial social interactions within the community.